Measurement of bony anatomical parameters of the distal ulna based on healthy adult data: A cross-sectional study - Li, Dengchen; Li, Xiaolin; Hou, Zexin; Pan, Fengman (Frontiers in Surgery, 2023)
【Abstract】Purpose This study sought to conduct several three-dimensional measurements of the distal ulna in healthy Han Chinese, providing the anatomical basis for the diagnosis and treatment of hand trauma, distal ulnar disorders, and the design of wrist prostheses Methods 50 Han Chinese men and women that underwent computed tomography (CT) scans of the distal ulnar carpus were included in the present study. A three-dimensional digital model of the distal ulna was reconstructed using Mimics software. Moreover, the anatomical data of 10 indicators were measured using MIMICS software. Each index data was measured by 2 investigators independently, and the average value was taken. The data were stratified and compared between left and right sides and men and women. Results A 3D digital model of the distal ulnar bone with a realistic shape was reconstructed. The 10 anatomical parameters measured are as follows:The length of the ulnar styloid process (posterior anterior),The length of the ulnar styloid process(anterior and posterior) ; the transverse diameter of the ulnar head ; the anteroposterior diameter of the ulnar head . The radial inclination angle of the ulna; the ulnar inclination angle ; the distal space between the ulna and radius; the ulnar notch angle of the lower radius . The anterior and posterior diameters of the ulnar notch of the lower radius, and the superior and inferior diameters of the ulnar notch of the lower radius. Statistical analysis showed no significant difference after stratification by laterality and gender. Conclusion our findings can providing the anatomical basis for the diagnosis and treatment of hand trauma, distal ulnar disorders and further improve currently available wrist joint prostheses.